Qualité des rôles sociaux et niveau d’anxiété chez les couples à double revenu - Lauzon, Anne-Marie; Cyr, Mireille (Canadian Journal of Counselling and Psychotherapy, 1993)
Contradictory conclusions have been reached by studies examining the influence of multiple social roles on stress. The present study examined the influence of quality of multiple roles on anxiety of dual-income couples; an attempt was also made to determine which of four roles occupied by men and women was the most stressful. A total of 94 couples meeting criteria for dual-income families completed different questionnaires measuring anxiety level and role quality (parental, work, domestic and marital roles). Results indicated that women were significantly more anxious than men. Hierarchical multiple regression analyses revealed that work was the most difficult role for men; parenthood was most strongly associated with anxiety for women. Theoretical implications of these findings are discussed.